2006
DOI: 10.1530/eje.1.02222
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrope hypersecretion coupled with cortisol hypo-responsiveness to stimuli is present in patients with autoimmune endocrine diseases: evidence for subclinical primary hypoadrenalism?

Abstract: Objective: In autoimmune polyglandular syndrome types 1, 2, and 4 primary adrenal insufficiency is present, but its diagnosis is often late. We investigated the function of the hypothalamic-pituitaryadrenal axis in a group of patients with autoimmune diseases (AP) without any symptoms and signs of hypoadrenalism. Design: In 10 AP and 12 normal subjects (NS), we studied cortisol (F), aldosterone (A), and DHEA responses to 0.06 mg adrenocorticotropin (ACTH) (1-24) followed by 250 mg, ACTH and F responses to huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…It was evidenced that local tissue bioavailability of F participates at regulation of many metabolic processes, including glucose metabolism and glycaemia [34,35]. The mechanism enabling to maintain normal adrenal cortisol secretion in immunopathies may be also compensatory increased ACTH stimulation [36]. It may be speculated that ACTH hypersecretion could play in LR a similar role for maintaining practically the same daily profile of salivary F as was found in NR.…”
Section: Discussionmentioning
confidence: 96%
“…It was evidenced that local tissue bioavailability of F participates at regulation of many metabolic processes, including glucose metabolism and glycaemia [34,35]. The mechanism enabling to maintain normal adrenal cortisol secretion in immunopathies may be also compensatory increased ACTH stimulation [36]. It may be speculated that ACTH hypersecretion could play in LR a similar role for maintaining practically the same daily profile of salivary F as was found in NR.…”
Section: Discussionmentioning
confidence: 96%
“…Certain inflammatory mediators induced by the process of beta‐cell autoimmune destruction are able to stimulate immune function and the HPA axis. This event could explain the increase in basal and stimulated ACTH in patients with autoimmune disease and no signs of hypocortisolism. The increased activity of the HPA axis in diabetic patients may be also attributable to an alteration of the release of ACTH by the corticotroph, in addition, to the action of corticotrophin releasing hormone (CRH) on the adrenal gland independent of the action of ACTH .…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial, it has been suggested that severely thyrotoxic patients might have an impaired cortisol response to insulin-induced hypoglycemia [5] and to both high and low-dose ACTH stimulation, associated or not with dexamethasone [6,7,13,34]. After normalization of thyroid function this impairment disappears, which suggests that adrenal autoimmune disease is an unlikely cause for the reduced adrenocortical reserve [7,13].…”
Section: Discussionmentioning
confidence: 99%